Projeto de uma fonte cc controlada de alta tensão - Farhat, Heitor (Universidade Federal de São Carlos, 2023)
This work presents the design of a high-voltage direct current (DC) power supply, intended for plasma generation and applications in metallic deposition processes on semiconductor materials, as well as research in the field of microelectronics. The application of metallic thin films through cathodic sputtering is widely used in various fields, including industrial part coating, cosmetic and decorative finishes, food packaging, jewelry, photovoltaic systems, and academic research. To address this need, a circuit was proposed consisting of an uncontrolled rectifier, followed by a controlled inverter with PWM filtering, a 60 Hz step-up transformer for high voltage, and an uncontrolled rectifier at the transformer’s secondary. This work presents the schematic diagram and printed circuit board (PCB) design of the power supply, the implemented control strategy, and simulation results analyzing the system’s performance. The simulations demonstrated that the system possesses the required characteristics for the sputtering process, operating safely under varying voltage levels and load conditions.
Design of a high-voltage controlled dc power supply
Keywords: Conversor CA-CC; Conversor CC-CA; Inversor; Controle digital; Fonte CC de alta tensão; ENGENHARIAS::ENGENHARIA ELETRICA::ELETRONICA INDUSTRIAL, SISTEMAS E CONTROLES ELETRONICOS